The semiotics of architecture in video games - Aroni, Gabriele 1985- (Bloomsbury advances in semiotics, 2024)
"Video games are among the most popular media on the planet, and billions of people inhabit these virtual worlds on a daily basis. This book investigates the architecture of video games, the buildings, roads and cities in which gamers play out their roles. Examining both the aesthetic aspects and symbolic roles of video game architecture as they relate to gameplay, Gabriele Aroni tackles a number of questions, including: How does digital architecture relate to real architecture? Where does the inspiration for digital gaming architecture come from, and how does it move into new directions? How does the design of virtual architecture influence gameplay and storytelling? Looking at how architecture in video games communicates and interacts with players, this book combines semiotics and architecture theory to display how architecture is used in a variety of situations, with different aims and results. Using case studies from NaissanceE , Assassin's Creed II and Final Fantasy XV , The Semiotics of Architecture in Video Games discusses the techniques used to create successful virtual spaces and proposes a framework to analyse video games architecture, ultimately explaining how to employ architectural solutions in video games in a systematic and effective way."